Asymmetric Synthesis of N‐Substituted 1, 2‐Amino Alcohols from Simple Aldehydes and Amines by One‐Pot Sequential Enzymatic Hydroxymethylation and Asymmetric Reductive Amination. Issue 17 (28th February 2022) - Li, Yu; Hu, Na; Xu, Zefei; Cui, Yunfeng; Feng, Jinhui; Yao, Peiyuan; Wu, Qiaqing; Zhu, Dunming; Ma, Yanhe
Abstract: The chiral N‐ substituted 1, 2‐amino alcohol motif is found in many natural and synthetic bioactive compounds. In this study, enzymatic asymmetric reductive amination of α‐hydroxymethyl ketones with enantiocomplementary imine reductases (IREDs) enabled the synthesis of chiral N ‐substituted 1, 2‐amino alcohols with excellent ee values (91–99 %) in moderate to high yields (41–84 %). Furthermore, a one‐pot, two‐step enzymatic process involving benzaldehyde lyase‐catalyzed hydroxymethylation of aldehydes and subsequent asymmetric reductive amination was developed, offering an environmentally friendly and economical way to produce N‐ substituted 1, 2‐amino alcohols from readily available simple aldehydes and amines. This methodology was then applied to rapidly access a key synthetic intermediate of anti‐malaria and cytotoxic tetrahydroquinoline alkaloids. Abstract : A one‐pot, two‐step enzymatic cascade reaction was developed for the synthesis of N‐ substituted chiral 1, 2‐amino alcohols from simple aldehydes and amines by coupling hydroxymethylation and reduction amination reactions. This methodology was then applied to rapidly access a key building block of various tetrahydroquinoline alkaloids of pharmaceutical importance.